The Microbiology of Presence: On the Art of Anna Zagrodzka - Domańska, Ewa (Farol, 2026)
This article analyzes Anna Zagrodzka's project Alternaria alternata, relating genocide, ecocide, and the conservation of Nazi extermination camps. Through an analysis of the artist’s photographs and frameworks from laboratory humanities and multispecies ethnography, it demonstrates how the art highlights processes of life’s adaptation and contributes to reflections on future scenarios amidst environmental and human crises.
Keywords: resilience; adaptation; arts of attention; Anna Zagrodzka; Polaroid photography